2010
DOI: 10.1007/s12576-010-0111-1
|View full text |Cite
|
Sign up to set email alerts
|

Control of ionic selectivity by a pore helix residue in the Kv1.2 channel

Abstract: Interaction between the selectivity filter and the adjacent pore helix of voltage-gated K(+) (Kv) channels controls pore stability during K(+) conduction. Kv channels, having their selectivity filter destabilized during depolarization, are said to undergo C-type inactivation. We examined the functionality of a residue at the pore helix of the Kv1.2 channel (V370), which reportedly affects C-type inactivation. A mutation into glycine (V370G) caused a shift in reversal potential from around -72 to -9 mV. The per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Together, these findings suggest that even sites at a distance from the selectivity filter can alter its static and dynamic properties. Interactions between the selectivity filter and adjacent domains are crucial determinants of C-type inactivation and ionic selectivity in potassium channels (35)(36)(37)(38)(39). Alkaline pH has been shown to cause functional "dilation" of the pore of TRPV5 through mechanisms apparently involving the pore helix (40).…”
Section: Discussionmentioning
confidence: 99%
“…Together, these findings suggest that even sites at a distance from the selectivity filter can alter its static and dynamic properties. Interactions between the selectivity filter and adjacent domains are crucial determinants of C-type inactivation and ionic selectivity in potassium channels (35)(36)(37)(38)(39). Alkaline pH has been shown to cause functional "dilation" of the pore of TRPV5 through mechanisms apparently involving the pore helix (40).…”
Section: Discussionmentioning
confidence: 99%
“…We had previously reported that mutations in the critical position 42 in Kcv NTS , which is equivalent to a functional hot spot for filter gating in KcsA (E71), MthK (V55), and Kv channels (V370 in Kv1.2 [ Chao et al, 2010 ]), alter key properties of this Kcv channel. In particular, the S42T mutant shows an increase in unitary conductance as well as a stabilization of the SF gate at hyperpolarizing voltages ( Rauh et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%